A CORPUS-BASED ANALYSIS OF FIRST-PERSON PRONOUN IN NIKI’S SONG - Mukminin, Muhamad Saiful; Fitri, Fajriani; Atikoh, Iklilah; Yaman, Nurinsani (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
This study aims to analyze the use of first-person pronouns in NIKI's song lyrics, focusing on their frequency, pattern, and context of usage. The research employs a descriptive qualitative-quantitative approach, combining corpus analysis with contextual interpretation. The data consists of song lyrics from NIKI's albums and popular tracks, formatted into a compatible text file (.txt) for analysis using AntConc software version 4.3.1. Data collection involved gathering lyrics from reliable sources, cleaning the data, and preparing it for analysis. The analysis process included identifying the frequency of first-person pronouns, observing distribution patterns through the concordance feature, and interpreting the context and meanings of pronoun usage. The findings reveal a dominance of the pronoun